The association of c-reactive protein with arterial compliance in asymptomatic young adults: the bogalusa heart study - Sharma, D; DasMahapatra, P; Fernandez, C; Chen, W; Srinivasan, S R; Xu, J; Berenson, G S (Journal of human hypertension, 2013)
Atherogeneis is a chronic progressive syndrome caused by endothelial dysfunction, vascular inflammation, vessel wall remodeling and eventual vascular flow compromise. Emerging data suggest that arterial compliance inversely correlates with atherogenesis and cardiovascular (CV) events. However, information is scant on the association of chronic systemic inflammation with arterial elasticity in young asymptomatic adults. The association of hsC-reactive protein (CRP) and central-vascular compliance was studied in 641 individuals (45.2% males; 71.8% whites), aged 31–43 years enrolled in the Bogalusa Heart Study. The measured variables included large-artery compliance (capacitive, C1), representative of the aorta and its major branches; and small-artery compliance (oscillatory, C2), representative of the distal part of the circulation; hsCRP, as a measure of systemic inflammation; along with traditional CV risk factor variables. Significant race and sex differences were noted for C1 (white males>black males P -value <0.0001; males>females P -value 0.04), C2 (whites>blacks P -value 0.0004; males>females P -value<0.0001) and hsCRP (blacks>whites P -value 0.03; females>males P -value 0.002). Mean values of C1 in subjects with high hsCRP levels (>3 mg l −1 ) were significantly lower than those with average (1–3 mg l −1 ) and low levels (<1 mg l −1 ) (14.2 ml per mmHg × 10 versus 15.2 ml per mm Hg × 10 versus 15.7 ml per mmHg × 10, P for trend=0.02), after adjusting for age, race, sex and body surface area (BSA). hsCRP showed a trend toward inverse correlation with C1 (−0.07, P =0.07) but no such trend for C2, after adjusting for race and sex. In the multivariate linear regression model, adding age, race, sex, BSA, mean arterial pressure, insulin resistance, lipoprotein variables and smoking status, the effect persisted between C1 and hsCRP ( β =−0.35, P =0.01). In an asymptomatic population of young adults, hsCRP predicts reduced large-artery compliance (C1). These findings support the role of systemic inflammation in early pathological changes in artery wall in atherogenesis. Small-artery compliance (C2) however did not correlate with hsCRP.